Construct of Carbon Nanotube-Supported Fe2O3 Hybrid Nanozyme by Atomic Layer Deposition for Highly Efficient Dopamine Sensing - Yang, Yingchun; Li, Tao; Qin, Yong; Zhang, Lianbing; Chen, Yao (Frontiers in Chemistry, 2020)
Fe2O3 nanozyme has been identified as the most promising alternative for Fe3O4 nanozyme due to its relatively low toxic risk and good chemically stability. However, its enzyme-like activity is relatively low to meet specific application requirements. Furthermore, previous synthesis approaches have difficulties in fabricating ultra-small Fe2O3 nanoparticles with tunable size and suffer from agglomeration problem. In this study, atomic layer deposition (ALD) was used to deposit Fe2O3 on surfaces of carbon nanotube to form hybrid nanozyme (Fe2O3/CNTs). The ALD enables the preparation of ultrafine Fe2O3 nanoparticles with precise size control less than 1 nm, while the CNTs could be served as promising support for good dispersibility, as well as effective activity activator. Hence, the formed Fe2O3/CNTs exhibits excellent peroxidase-like activity with specific peroxidase activity of 24.5 U mg-1. A colorimetric method for sensing of dopamine (DA) was established and presented good sensitivity with a limit of detection (LOD) as low as 0.11 μM. These results demonstrated that, in virtue of the meticulous engineering method like ALD, carbon nanomaterials-based hybrids can be developed as talented enzyme mimetic, thus paving way for nanozyme design with desired activity and broadening their applications in biosensing and other fields.